How Do Fatty Acids Cause Allosteric Binding of Drugs to Human Serum Albumin? - Chuang, Victor; Otagiri, M. (AAPS, 2002)
Purpose. This study was undertaken to investigate how fatty acids cause the allosteric binding of drugs to human serum albumin (HSA). The influence of fatty acids on the binding of ketoprofen (KP), an NSAID, to HSA was examined by using a photoaffinity labeling technique. Methods. Ultrafiltration was performed to quantitate the concentration of free KP. HSA, photolabeled with KP in the presence of myristate (MYR), octanoate, and diazepam, was cleaved with cyanogen bromide, separated by Tricine sodium dodecyl sulfate polyacrylamide gel electrophoresis and subsequently analyzed by autoradiography.Results. The addition of MYR at molar ratios from 4 to 5, but not from 1 to 2, causes substantial increases in unbound KP for KP:HSA ratios of 0.5 and 1. The addition of two or more moles of MYR, octanoate, and diazepam per mole of HSA caused a pronounced decrease in the labeling of the 11.6- and 13.5-kDa peptides. However, only MYR showed an increase in labeling of the 20 kDa and, especially, the 9.4-kDa peptides. At MYR:HSA ratios in excess of 3, a decrease in the extent of labeling of the 9.4-kDa peptide was observed. Conclusion. Long-chain fatty acids regulate the binding properties of HSA in a complex manner, in which a simultaneous competitive and allosteric mechanism operates and which mainly involves domain I.